Autoantibodies to Peptidylarginine Deiminase 2 Are Associated With Less Severe Disease in Rheumatoid Arthritis - Darrah, Erika; Giles, Jon T.; Davis, Ryan L.; Naik, Pooja; Wang, Hong; Konig, Maximilian F.; Cappelli, Laura C.; Bingham, Clifton O.; Danoff, Sonye K.; Andrade, Felipe (Frontiers in Immunology, 2018)
Objectives: Peptidylarginine deiminases (PAD) 2 and 4 are key enzymes in rheumatoid arthritis (RA) pathogenesis due to their ability to generate the protein targets of anti-citrullinated protein antibodies (ACPA). Anti-PAD4 antibodies that cross-react with PAD3 (anti-PAD3/4) have been identified and are associated with severe joint and lung disease. Here, we examined whether anti-PAD2 antibodies were present in patients with RA and defined their clinical significance. Patients and Methods: A PAD2 ELISA was established to screen for anti-PAD2 IgG in sera from RA patients from a prospective observational cohort study (n=184) and healthy controls (n=100). RA patient characteristics were compared according to anti-PAD2 antibody status. Multivariable models were constructed to explore the independent associations of anti-PAD2 antibodies with clinical variables. Results: Anti-PAD2 antibodies were found in 18.5% of RA patients and 3% of healthy controls (p<0.001). Among RA patients, anti-PAD2 antibodies were not associated with traditional genetic or serologic RA risk factors, including HLA-DRβ1 shared epitope alleles, ACPA, rheumatoid factor (RF), or anti-PAD3/4 antibodies. In addition, antibodies to PAD2 were associated with fewer swollen joints, a lower prevalence of interstitial lung disease, and less progression of joint damage. In subset analyses in which patients were stratified by the baseline presence of ACPA/RF or anti-PAD3/4 antibodies, anti-PAD2 antibodies provided additional value in identifying patients with the least progressive joint disease. Conclusion: Anti-PAD2 antibodies represent a novel serologic marker in RA that identifies a genetically and clinically unique subset of patients with less severe joint and lung disease.